Adoptability of Korean PPP scheme from the recipient's perspective - Lee, Jisun (KDI School, 2011)
In trying to have the lessons from the Korean PPP and developing countries’ actual circumstances communicated, this paper conducts an online-survey on the adoptability of the Korean infrastructure public private partnerships (PPPs) scheme. This paper traces five root constraints in adopting the Korean infrastructure PPP scheme from the recipient’s perspective and gives tailored solutions derived from the Korean PPP experiences regarding these constraints. It provides policy makers with a road map for making efficient use of ODA to achieve better PPPs as well as tangible development that require governance and entrepreneur spirit to tango.
Thesis(Master) --KDI School:Master of Public Policy,2011
Keywords: PPP(Public Private Partnerships)